“I Can’t Wait for You to Die”: A Community Archives Critique - Apple, Harrison (Archivaria, 2021)
Stemming from conflicts over the authority of professional archives to arrange and steward community knowledge, this article outlines the limitations of the archival apparatus to produce the conditions for social liberation through acquisition and offers suggestions for how to operate otherwise, as a collaborator in forgetting. It discusses the origins and revised mission of the Pittsburgh Queer History Project (PQHP) as a reflection of the precarious definition of community archives within the discipline and field of archival science. By retracing the steps in the PQHP’s mission, as it moved from being a custodial and exhibit-focused collecting project to acting as a decentralized mobile preservation service, I argue that community archival practice is an important standpoint from which to critically reassess the capacity of institutional archives to create a more conscious and complete history through broader collecting. Specifically, I demonstrate how contemporary attention to the value of community records and community archives is frequently accompanied by a demand for such archives, records, and communities to confess precarity and submit to institutional recordkeeping practices.